Incidence and Risk Factor of Unintentional Fall Related Injuries Among Children in Tamil Nadu, India - P, Manoj; Muthunarayanan, Logaraj; Palanisamy , Kaveri (National Journal of Community Medicine, 2023)
Introduction: Injuries are a major global public health problem. There are very few community-based studies on childhood injury from India in this study, we identified the distribution and risk factors for fall-related child injuries in the Chengalpattu district, Tamil Nādu community. Methodology: A descriptive analysis was done among 710 children of age up to 14 years residing in the Kattankulathur region in Tamil Nādu. The appropriate number of samples were recruited using the cluster sampling method by dividing the subjects into separate clusters and from each cluster 40 samples were obtained. The information on fall-related injury was collected according to mechanism of ‘injury’ Results: The annual incidence of fall-related injuries was 9.1 %. About 72.3% of children had injuries at home and 36% of the persons had fractures in the upper limb. 42% of children had disability in their hands. The age, gender, education and type of family was significant to injury. Conclusion: Our study reported a higher incidence of Fall injuries in Tamil Nādu when compared other studies done in India. Male children are the most common victims of injury and also identified homes, roads/streets as the most common places for the occurrences of fall injury in children.